Characterisation of the RNA Polymerase Subunits E and F from the Antarctic Archaeon Methanococcoides Burtonii - De Francisci, Davide (UNSW Sydney, 2010)
The archaeal RNA polymerase (RNAP) is composed of eleven or twelve subunits and is closely related to the eucaryal RNAPs (particularly RNAP lI). Nine or ten of these subunits form the core holoenzyme, and the remaining two subunits, E and F, form a dissociable heterodimer whose functional contribution to transcription remains poorly understood. In yeast, the corresponding heterodimer, Rpb4/7, functions in nuclear transcription-coupled transport of specific mRNA species to the cytoplasm, enabling RNA degradation. While the ability of this heterodimer to bind RNA has been demonstrated, whether it can recognise specific RNA targets has not been determined. In this study the recombinant archaeal heterodimer from the Antarctic archaeon Methanococcoides burtonii (MbRpoE/F) has been characterised by comparison with its thermophilic homologue from Methanocaldococcus jannaschii (MjRpoE/F). The structural analysis showed that MbRpoE/F is far less stable and more flexible than MjRpoE/F. Crystallising conditions were also found for MbRpoE/F and a complete in-house 3.2 Å data set was collected, although it was impossible to solve the structure. Functional comparison of these two heterodimers was performed by electrophoretic mobility shift assay (EMSA), and provided a preliminary indication that the archaeal RpoE/F heterodimers have the capacity to bind ssDNA in a sequence-dependent manner. Following the EMSA findings, it became essential to determine the nucleic-acid binding characteristics of MbRpoE/F, with the aim of learning about the nucleic-acid targets it was capable of interacting with. His-tagged MbRpoE/F was incubated with whole cell RNA, and complexes were purified using Ni-NTA. The bound RNA was eluted, labeled and hybridised to a high-density M. burtonii microarray, and 11 8 genes were identified (4% of the total genome). The genes were divided into distinct categories: methanogenesis, nucleotide metabolism, cofactors biosynthesis, transcription, translation, import/export and others; most importantly, for each category the genes identified appear to code for key regulatory enzymes in the same category. This suggested that MbRpoE/F is indeed capable of binding RNA in a specific manner and that the polymerase heterodimer also has a regulatory effect within the physiology of the archaeon. Due to the high level of structural and functional similarities between the E/F subunits with their eucaryal homologues, the implication of these findings may be that an important function of the eucaryal and archaeal heterodimers is to directly regulate the abundance of specific classes of cellular mRNA via this specific binding.